2021
DOI: 10.1097/aco.0000000000001088
|View full text |Cite
|
Sign up to set email alerts
|

Donation after cardiac death in heart transplantation: is there an ethical dilemma?

Abstract: Purpose of reviewIn an attempt to address the organ shortages in heart transplantation, USA centres have begun utilizing donation after cardiac death (DCD) as an alternative to traditional donation after brain death (DBD). As this paradigm continues to expand, there is a need to address the medico-legal and ethical aspects of DCD donation, which is the focus of the current review. Recent findingsCurrent protocols use criteria established by the Uniform Determination of Death Act (UDDA), which is explicit in de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
(21 reference statements)
0
1
0
Order By: Relevance
“…However, all DCD HT involves the restarting of the previously "irreversibly dead" heart. Some authors have questioned whether this, by necessity, negates the previous determination of death as the patient may not meet death criteria from a biological systems perspective of irreversibility [14,154,155]. While a full exploration of these ethical questions is beyond the scope of this review, it has been suggested that modern techniques including ex situ heart perfusion and donor normothermic regional perfusion have assuaged legal concerns and created a more stable ethical framework for DCD HT [15].…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…However, all DCD HT involves the restarting of the previously "irreversibly dead" heart. Some authors have questioned whether this, by necessity, negates the previous determination of death as the patient may not meet death criteria from a biological systems perspective of irreversibility [14,154,155]. While a full exploration of these ethical questions is beyond the scope of this review, it has been suggested that modern techniques including ex situ heart perfusion and donor normothermic regional perfusion have assuaged legal concerns and created a more stable ethical framework for DCD HT [15].…”
Section: Ethical Considerationsmentioning
confidence: 99%
“…Despite the fact that DCD donors are becoming more common [14,15], after years of work establishing and refining protocols [16], deep-rooted ethical concerns remain amongst healthcare providers and the general public [13,17]. Cardounel et al , [18] (Ref. pp.…”
mentioning
confidence: 99%